EFEKTIVITAS GEL EKSTRAK ETANOL BAWANG PUTIH (Allium sativum L.) TERHADAP BAKTERI Staphylococcus aureus - Dewi, Irene Puspa; Orde, Ilham Maslan; Verawaty, Verawaty (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Garlic (Allium sativum L.) is one of the traditional medicines which has an antibacterial efficacy compound namely Allisin which is able to inhibit the growth of Staphylococcus aureus bacteria. This study aims to formulate the garlic bulb extract into a good gel preparation for use as an acne drug and to determine the antibacterial effectiveness of the ethanol extract of garlic gel against the bacterium Staphylococcus aureus using the wells method. The gel evaluation was carried out to meet the requirements with organoleptic test parameters, homogeneity, pH, spreadability, adhesion and irritation test. This study uses extracts of 10% and 20% concentrations, at each concentration being able to inhibit the growth of Staphylococcus aureus bacteria. In the formula, the concentration of 20% has a inhibition zone diameter of 1.59 cm and a concentration of 10% has a inhibition of 1.50 cm. Statistical test results using the One Way ANOVA test found that there was no significant difference between the average diameter of inhibition of garlic extract gel concentration of 10% with a concentration of 20%.